The Impact of Training, Workload, and Career Development on Job Satisfaction and Employee Performance: Evidence from Banco Nacional de Comércio de Timor-Leste (BNCTL) - Isabel Agustina Zaka (Universitas Pelita Harapan, 2025)
This study investigates the influence of training, workload, and career development on job satisfaction and employee performance at Banco Nacional de Comércio de Timor-Leste (BNCTL). As Timor-Leste’s state-owned commercial bank, BNCTL plays a strategic role in financial inclusion and national economic development. Rapid modernization—branch expansion, digital banking, and international card products—creates both opportunities and human resource challenges. Using a quantitative, explanatory, cross-sectional design, this study employs stratified random sampling of 250 employees across branches and headquarters. Data will be collected through structured questionnaires and analyzed using SEM and regression models, including mediation and moderation testing. The research is expected to provide empirical evidence on how HR practices affect employee outcomes in small, post-conflict economies. Findings will contribute academically by extending HRM theories to developing country contexts, and practically by guiding BNCTL’s HR strategies in training investment, workload calibration, and transparent career pathways.